BERKENALAN DENGAN TASAWUF - Asep Rifqi Fuad (Jurnal Al Burhan, 2021)
Sufism is one of the sciences that does not get attention among Muslim students, in it is the third element (Islam, Faith and Ihsan) which is very important in Islam, because Sufism is an elaboration of the value of "Ihsan". Judging from the perceptive needs and knowledge sufism remains important. In Islam, man consists of three elements, namely the body or body, reason and ruhani. So there are three types of human needs, namely the needs of bodies, the needs of reason and the needs of ruhani. The need for conscience is ?ikrullâh, and ?ikrullâh is the focus of sufism studies, so with Sufism man seeks to meet the needs of ruhaninya. Keyword: Tasawuf, Ihsân, Ruhani, ?ikrullâh